Recurrent aneurysmal fibrous histiocytoma. Issue 3 (27th February 2004) - Sheehan, K M; Leader, M B; Sexton, S; Cunningham, F; Leen, E
Abstract : Aneurysmal fibrous histiocytoma is a rare variant of cutaneous fibrous histiocytoma that results from blood vessel proliferation and haemorrhage into a fibrous histiocytoma. The resulting lesion has a very different clinical appearance, hence the potential confusion with other skin lesions. This report describes the case of a 48 year old woman with a recurrent fibrous histiocytoma with prominent vasculature, which over a three year period recurred on two occasions, showing more progressive features of the aneurysmal variant. In addition, squamous lined cysts were present within this tumour, a finding that has not been described previously. The histological features of this rare lesion and the importance of the differential diagnosis from other similar appearing malignant lesions will be discussed.